Lessons Learned in Disaster Risk Management from the Perspective of Citizen Participation - Canese de Estigarribia, Marta Isabel; Prieto Granada, Violeta; Brítez, Alberto; Vuyk Espínola, Cecilia María; Lezcano, José; Chamorro, Romilio (Revista del CLAD Reforma y Democracia, 2021)
This research aims to analyze the lessons learned in risk management from the perspective of citizen participation in the 13 municipalities that form the metropolitan área of Asunción. The research had a qualitative approach with a descriptive scope. It was developed through in-depth interviews with municipal officials involved in risk management and documentary analysis. The data obtained were grouped into analysis categories and processed by means of technological tools. The analysis of the results indicates that the development of local risk management, in almost all the municipalities of the metropolitan area of Asunción lacks operating units, specific regulations and an adequate budget. Lessons learned recognize organizational experiences, the formation of networks and the identification of attitudinal barriers to effective citizen participation in risk management.
Keywords: Risk Management; Risk; Disaster Management; Citizen Participation; Municipalities; Case Analysis; Paraguay